2018
DOI: 10.1016/j.chiabu.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and neglect in institutional settings, cumulative lifetime traumatization, and psychopathological long-term correlates in adult survivors: The Vienna Institutional Abuse Study

Abstract: Child maltreatment (CM) in foster care settings (i.e., institutional abuse, IA) is known to have negative effects on adult survivor's mental health. This study examines and compares the extent of CM (physical, emotional, and sexual abuse; physical and emotional neglect) and lifetime traumatization with regard to current adult mental health in a group of survivors of IA and a comparison group from the community. Participants in the foster care group (n = 220) were adult survivors of IA in Viennese foster care i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 36 publications
7
55
2
2
Order By: Relevance
“…Similarly, Lueger‐Schuster et al. () found that being in foster care was associated with poor education outcomes and mental disorders in children. In our study, the results did not suggest that these left‐behind children would develop DTD, but it was interesting to discover their tendency to exhibit DTD‐like symptoms.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Lueger‐Schuster et al. () found that being in foster care was associated with poor education outcomes and mental disorders in children. In our study, the results did not suggest that these left‐behind children would develop DTD, but it was interesting to discover their tendency to exhibit DTD‐like symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…Parental absence may be a chronic stressor for children whose parents have left, because it decreases positive relationships and causes gaps in communication with parents (Kwaka, Kim, & Yoonc, ) and emotional bonding and support, thus hindering their development in various ways (e.g., Lueger‐Schuster et al., ). Given that there are multiple causes of parental absence (e.g., divorce, parental mortality, migration, or out‐of‐wedlock birth), we specifically focused on parental absence via migration.…”
mentioning
confidence: 99%
“…However, it is clear that child maltreatment taking place in these settings affects the lives of both victims, their families and their communities-at times for generations. Child maltreatment has a negative impact on the physical, mental, spiritual, educational and economic wellbeing of those experiencing and surviving it-both in the short term and in the form of long-term consequences that reduce the quality of life during adulthood (Lueger-Schuster et al, 2018). In recent years, child maltreatment occurring in institutional settings has received substantial attention both at the policy level, amongst practitioners and service agencies working with children in different capacities and roles, and as part of the public debate.…”
Section: Condition or Issuementioning
confidence: 99%
“…This can ultimately affect the child's long-term health-related quality of life and lead to problems such as depression, substance abuse, anxiety and suicidal behavior, increased risk of sexually transmitted diseases, and even cancer [9][10][11][12] . Adolescents who have been physically abused are more likely to show increased of externalizing problems and criminal offending 13,14 . In addition, adolescents and adults who had experienced physical and/or sexual abuse in their childhood are four times more likely to have suicidal ideation, than their peers who had not experienced such abuses 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adolescents and adults who had experienced physical and/or sexual abuse in their childhood are four times more likely to have suicidal ideation, than their peers who had not experienced such abuses 2 . Furthermore, among adults who had been physically abused as children there is a higher degree of aggression compared with adults who had not been abused 13,14 . Physical punishment of children are very frequent in East Asia and the Pacific region including Cambodia 2 .…”
Section: Introductionmentioning
confidence: 99%